Green catalytic conversion of bio-based sugars to 5-chloromethyl furfural in deep eutectic solvent, catalyzed by metal chlorides. Issue 32 (14th March 2016) - Zuo, Miao; Li, Zheng; Jiang, Yetao; Tang, Xing; Zeng, Xianhai; Sun, Yong; Lin, Lu
Abstract : 5-Chloromethylfurfural (5-CMF) was effectively prepared from fructose and other carbohydrates in a biphasic reaction system, which was composed of methyl isobutyl ketone (MIBK) and deep eutectic solvent (DES) with catalyst of AlCl3 ·6H2 O. Abstract : 5-Chloromethylfurfural (5-CMF), a biomass-derived platform chemical with great potential applications, was synthesized by a novel method from sugars, using metal chlorides as catalysts in a deep eutectic solvent (DES). AlCl3 ·6H2 O was verified as the most effective catalyst among various metal chlorides, and provided a 5-CMF yield of 50.3% along with 8.1% 5-HMF yield at 120 °C in 5 h. By this green, mild and cost-effective approach, the dependence of 5-CMF production on the large amount and high concentration of hydrochloric acid in previous studies was eliminated.